Hamka’s Review of Economic Verses in Tafsir Al-Azhar Using the Ijtimā‘ī Methodological Approach - Abur Hamdi Usman; Mohd Farid Ravi Abdullah; Mazlan Ibrahim; Azwar Iskandar (Studia Quranika, 2022)
Tafsir al-Azhar is a well-known work of Indonesian exegete, Hamka. This study examines one of Hamka’s magnum opus exegetical works. The emphasis is on his discussion of economic matters, particularly capitalism, usury, and corruption, particularly in the selected text. This study employs a qualitative approach, analyzing chosen documents. This study revealed that Hamka’s techniques are unique due to to Indonesia's socio-cultural characteristics. Hamka employed the al-Ijtimā‘ī method in his writing, as do other exegetes. This method aimed to comprehend the Quran by carefully examining its terms and expanding their meanings beautifully and engagingly anguage within the context of the existing cultural system.